Echocardiographic Evaluation of left Ventricular Function Following Late Percutaneous Coronary Intervention after Acute Anterior Myocardial Infarction with Left Ventricular Systolic Dysfunction (Bangladesh Heart Journal, 2018)
Background: The effect of late percutaneous coronary intervention on left ventricular function is incompletely understood.Objectives: To evaluate the effect of late Percutaneous Coronary Intervention on LV systolic function following coronary stenting after acute anterior myocardial infarction.Methods: A total of 60 patients, > 24 hours to 6 weeks after anterior AMI who attended in UCC, BSMMU between July 2014 to June 2015 were included in this study. They underwent coronary stenting. After coronary stenting all patients were in TIMI flow-3. Serial echocardiographic assessment of LV function before and after late intervention with modified Simpson’s rule in apical 4 chamber view as well as comparison between baseline result with that of after intervention were done. The patients were on standard medical therapy in post intervention period.Result: Mean age was 54.3±8.91 years with minimum 30 years and maximum 75 years. Most of the patients were male (67%). LVESV was 60.0±14.4 ml before PCI and 58.3±15.3 ml at discharge (p value 0.091) & 44.1±17.6 ml after 3 months (p value